(untitled) (Clinics, 2021)
OBJECTIVES: Ischemia and reperfusion (I/R) in the intestine could lead to severe endothelial injury, compromising intestinal motility. Reportedly, estradiol can control local and systemic inflammation induced by I/R injury. Thus, we investigated the effects of estradiol treatment on local repercussions in an intestinal I/R model. METHODS: Rats were subjected to ischemia via the occlusion of the superior mesenteric artery (45 min) followed by reperfusion (2h). Thirty minutes after ischemia induction (E30), 17b-estradiol (E2) was administered as a single dose (280 mg/kg, intravenous). Sham-operated animals were used as controls. RESULTS: I/R injury decreased intestinal motility and increased intestinal permeability, accompanied by reduced mesenteric endothelial nitric oxide synthase (eNOS) and endothelin (ET) protein expression. Additionally, the levels of serum injury markers and inflammatory mediators were elevated. Estradiol treatment improved intestinal motility, reduced intestinal permeability, and increased eNOS and ET expression. Levels of injury markers and inflammatory mediators were also reduced following estradiol treatment. CONCLUSION: Collectively, our findings indicate that estradiol treatment can modulate the deleterious intestinal effects of I/R injury. Thus, estradiol mediates the improvement in gut barrier functions and prevents intestinal dysfunction, which may reduce the systemic inflammatory response.